Wet Clutch Friction Interfaces under Water-Contaminated Lubricant Conditions. Issue 3 (3rd May 2016) - Fatima, N.; Marklund, P.; Mathew, A. P.; Larsson, R.
ABSTRACT: The performance of wet clutches used for automatic transmissions or other applications usually includes the desired positive friction characteristics and a shudder-free torque generation. Changes in the operating variables such as the lubricant conditions influence the formation of a tribofilm, and friction characteristics and can alter the degradation of the friction interfaces. In this work, the friction characteristics and degradation of the paper–steel friction interfaces were monitored when a commercial fully formulated automatic transmission fluid (ATF) was contaminated with water. It was found that water in ATF influenced the clutch stability by increasing the mean coefficient of friction (µ) and the negative friction–velocity slope. Surface studies of the posttest friction interfaces clearly indicated reduced surface porosity and permeability, increased wettability, and changed elemental composition on the contacting surfaces after tested with water-contaminated ATF. Moreover, water-contaminated paper liners' thermal decomposition shifted to a lower temperature compared to an uncontaminated liner during thermal analyses. These results displayed faster degradation and reduced service life of the clutch friction interfaces due to water contamination. The resultant surface condition can be associated with the observed unstable friction and negative friction–velocity slopes.